Effect of Cultural Organization, Compensation, and Performance of Teachers Pedagogical Vocational Business and Management in Tegal - Habibi, Beni; Samsudi, Samsudi; Raharjo, Tri Joko; Rusdarti, Rusdarti (The Journal of Educational Development, 2016)
This study aimed to influence organizational culture of schools, the amount of compensation received by the influence of teachers, the magnitude of the influence of pedagogical competence held by teachers on teacher performance and simultaneous influence of school culture, compensation, and pedagogical competence of the teachers performance Vocational Business and management in Tegal. Descriptive statistical analysis of the results of school organizational culture variables mean of 83.9298 either category or 61.40 %, 72.2544 compensation either category or 50.00 %, 85.1667 pedagogic either category or by 59.65 % and teacher performance is obtained mean of 99.9737 higher category or by 67.54 %. There is a positive and significant influence, school organizational culture, compensation and pedagogical competence of the teachers performance by 46.8 %. Influence of the organizational culture on the performance of the teacher is the smallest. Related to compensate teachers should understand and realize that through a raise, educator certification, and incentive routine of school should be a trigger spirit to maintain the performance of teachers.